2015
DOI: 10.1186/s12934-015-0252-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of a tyrosine-overproducing yeast platform using targeted metabolomics

Abstract: BackgroundL-tyrosine is a common precursor for a wide range of valuable secondary metabolites, including benzylisoquinoline alkaloids (BIAs) and many polyketides. An industrially tractable yeast strain optimized for production of L-tyrosine could serve as a platform for the development of BIA and polyketide cell factories. This study applied a targeted metabolomics approach to evaluate metabolic engineering strategies to increase the availability of intracellular L-tyrosine in the yeast Saccharomyces cerevisia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 53 publications
0
77
0
Order By: Relevance
“…First, we show that tyrosine and tryptophan levels limit the system; thus, increasing aromatic amino acid supply via introduction of feedback-resistant enzyme mutants in aromatic amino acid metabolism, such as Aro4, 70 or utilizing a tyrosine overproducing strain, 71 should enable straightforward increases in amino acid mono-oxidation. Second, our system does not currently take advantage of the power of the BH 4 recycling system, as biogenic amine levels are similar in the presence and absence of the recycling system.…”
Section: ■ Discussionmentioning
confidence: 99%
“…First, we show that tyrosine and tryptophan levels limit the system; thus, increasing aromatic amino acid supply via introduction of feedback-resistant enzyme mutants in aromatic amino acid metabolism, such as Aro4, 70 or utilizing a tyrosine overproducing strain, 71 should enable straightforward increases in amino acid mono-oxidation. Second, our system does not currently take advantage of the power of the BH 4 recycling system, as biogenic amine levels are similar in the presence and absence of the recycling system.…”
Section: ■ Discussionmentioning
confidence: 99%
“…4). 68 Gold et al 69 also realized a high yield of L-Tyr in S. cerevisiae by a strategy of combining localized pathway engineering with global engineering of central metabolism. Olson et al 67 reported that deletion of pheA encoding chorismate mutase/prephenate dehydratase and its leader peptide gene pheL resulted in a significant increase in L-Tyr production.…”
Section: Production Of L-tyr Derivativesmentioning
confidence: 99%
“…After optimizing the fermentation conditions, the titer of L-Tyr increased to 55 g L −1 in a 200 L fermenter. 68 Gold et al 69 also realized a high yield of L-Tyr in S. cerevisiae by a strategy of combining localized pathway engineering with global engineering of central metabolism. L-Tyr accumulated up to 192 mmol L −1 in the cytosol.…”
Section: Production Of L-tyr Derivativesmentioning
confidence: 99%
“…Metabolomics therefore may be used to complement current metabolic engineering strategies for optimizing biological production of chemicals within microorganisms (Oldiges et al, 2007;Putri et al, 2013). Through the detection of relevant metabolic perturbations, metabolomics can identify specific targets for strain improvement that may include detection of pathway bottlenecks, metabolite or product toxicity, imbalanced cofactor supply, or draining of metabolites by alternative pathways (Gold et al, 2015;Hasunuma et al, 2011;Korneli et al, 2012;Noguchi et al, 2016;Ohta et al, 2015;Teoh et al, 2015;Xu et al, 2016). Furthermore, metabolomics provides a comprehensive analysis of the metabolome that allows a deeper understanding of cellular metabolism and how gene modifications can be used for metabolic engineering.…”
Section: Introductionmentioning
confidence: 99%